AIMING MILLENIAL AND ZILLENIAL GENERATIONS THROUGH THE REBRANDING OF NATIONAL POPULATION AND FAMILY PLANNING BOARD - Rizky Fauzia (Lembaga Riset dan Pengkajian Strategi Pemerintahan IPDN, 2021)
This study aims to describe the rebranding process of the National Population and Family Planning Board (BKKBN) using descriptive qualitative research methods. The data collection technique was carried out by means of document study and field observation. The results showed that the BKKBN rebranding had already started in 2009 after the reformation period or after the implementation of Regional Autonomy in Indonesia. However, in 2019 BKKBN initiated a rebranding formality in institutional regulations. This research describes in detail the implementation of BKKBN rebranding by carrying out four elements of rebranding, namely repositioning, renaming, redesigning, and relaunching. The results showed that the repositioning of the BKKBN was carried out by determining the target segmentation of the BKKBN audience that focused on the millennial and zillenial generations and changing the position of the BKKBN from fertility issues to